PEMBERIAN SCAFFOLDING UNTUK MENGATASI HAMBATAN BERPIKIR SISWA DALAM MEMECAHKAN MASALAH ALJABAR - Khusnil Khatimah; Cholis Sadijah; Hery Susanto (Jurnal Kajian Pembelajaran Matematika, 2017)
This research objective is to describe students’ thinking barriers and to describe given scaffolding to overcome students’ experienced thinking barriers. This is a descriptive qualitative research. Research subjects is 2 students whose thinking capability is high and low. Documents being studied are students’ test result, unstructured interviews transcripts, ands scaffolding. This research demonstrates that subject 1 (S1) barriers are caused by the lack of analogical thinking capability on understanding problem, the low connecting capability when implementing solving plan, and the lack of existing knowledge and connection capability on re-examine planned procedure on problem solving. Subject 2 (S2) thinking barriers are caused by the low analogical capability in understanding problem, the lack of connecting capability when planning problem solving strategy, the lack of analogical capability in planning problem solving, and the lack of prior knowledge and connection in re-examine chosen procedure. Adjusting Anghileri’s scaffolding, S1 was given scaffolding at a rate of explaining and developing conceptual thinking, while S2 was given scaffolding at a rate of explaining, reviewing, restructuring, and developing conceptual thinking.